Insights from recent gravity satellite missions in the density structure of continental margins – With focus on the passive margins of the South Atlantic - Götze, Hans-Jürgen, Prof. Dr.; Pail, Roland, Prof. Dr. (Gondwana Research, 2017)
We focus on new gravity and gravity gradient data sets from modern satellite missions GOCE, GRACE and CHAMP, and their geophysical interpretation at passive continental margins of the South Atlantic. Both sides, South Africa and South America, have been targets of hydrocarbon exploration and academic research of the German Priority Program SAMPLE (South Atlantic Margin Processes and Links with onshore Evolution). The achievable spatial resolution, driven by GOCE, is 70–80 km. Therefore, most of the geological structures, which cause a significant gravity effect (by both size and density contrast), can be resolved. However, one of the most important aspects is the evaluation of the omission error, which is not always in the focus of interpreters. It results from high-frequency signals of very rough topographic and bathymetric structures, which cannot be resolved by satellite gravimetry due to the exponential signal attenuation with altitude. The omission error is estimated from the difference of the combined gravity model EIGEN-6C4 and the satellite-only model GOCO05S. It can be significantly reduced by topographic reductions. Simple 2D density models and their related mathematical formulas provide insights in the magnitude of the gravity effect of masses that form a passive continental margin. They are contrasted with results from satellite-only and combined gravity models. Example geophysical interpretations are given for the western and eastern margin of the South Atlantic Ocean, where standard deviations vary from 25 to 16 mGal and 21–11 mGal, respectively. It could be demonstrated, that modern satellite gravity data provide significant added value in the geophysical gravity data processing domain and in the validation of heterogeneous terrestrial data bases. Combined models derived from high-resolution terrestrial gravity and homogeneous satellite data will lead to more detailed and better constrained lithospheric density models, and hence will improve our knowledge about structure, evolution and state of ...